Swiss Biotech Day, May 2022. Sustainability Across the Pharmaceutical Value Chain - How Switzerland Could Take a Leading Role in Promoting a Greener Approach - Marta Gehring; Hans-Peter Meyer (CHIMIA, 2022)
The sustainability of the pharmaceutical industry has aroused interest from various sectors and disciplines, including chemistry, biology and engineering. Given the Swiss drug sector’s innovative engine and enormous economic importance, a Swiss Biotech Day panel discussion was held in May 2022 in Basel to address the question of how “sustainability across the pharmaceutical value chain” can be edged forward in Switzerland. Roche, Lonza, Pheida, ETH, the Swiss Academy of Engineering Sciences (SATW), and a newly established collaborative, Circular Carbon for Chemistry (ccLoop) joined forces and agreed that sustainability must become a key strategic goal for the industry in Switzerland. The panel looked at the sustainability challenge, at how a green transition can be achieved faster, and at how industrial biotechnology applications can improve industry’s performance, energy efficiency and product value while yielding viable sustainable solutions to protect our environment. Switzerland is a leader in drug development and manufacturing. By placing greater energy and resources on the sustainability equation, we ensure continued leadership and a greener world. ‘Swissness’ will increasingly have to denote effective drugs produced sustainably.